Clinical Efficacy of Articaine and Lignocaine Hydrochloride for Pudendal Nerve Block in Bullock - Ambhore, V. D.; Chepte, S. D.; Karad, N. M.; Bontalwad, G. M.; More, S. D.; Nakade, S. N.; Ghuge, A. R.; Raut, S. U.; Karad, G. G. (International Journal of Bio-resource and Stress Management, 2025)
The study was carried out during September, 2023 to February, 2024 at the Veterinary Clinical Complex, College of Veterinary and Animal Sciences, MAFSU Parbhani, Maharashtra, Indiato compare the clinical efficacy of Articaine and Lignocaine Hydrochloride for Pudendal Nerve Block in Bullocks. A total of 12 clinical cases with affections of penis, scrotum and prepuce were included in the study, these cases were randomly divided into two distinct groups (n=6). Group 1 was administered 4% articaine hydrochloride (1 mg kg-1), whereas Group 2 was given 2% lignocaine hydrochloride at the same dosage. The animal was restrained in standing position and pudendal nerve block was performed on both sides.The onset of action was notably faster in Group 1 (p≤0.01) as compared to Group 2, while prolonged duration of action was reported in Group 2 (p≤0.01) as compared to Group 1. The speed and extent of drug dispersion in Group 1 were more rapid and consistent compared to Group 2, resulting in a larger area of desensitization. Clinico-physiological and haemato-biochemical parameters were taken at 0, 20, 40, and 60-minute intervals. The mean heart rate, Rectal temperature and Respiratory rate showed non-significant changes. Similarly, haemoglobin and packed cell volume along with AST, ALT BUN and Creatinine displayed non-significant (p≥0.05) changes in either group throughout the study.